2009
DOI: 10.1007/s00464-009-0553-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance in flexible sigmoidoscopy: medical and nonmedical endoscopists

Abstract: This study has shown that clinical impression of endoscopist during FS regarding position is not very accurate, implying need for regular quality assurance. The technique of applying endomucosal clips with follow-on abdominal X-ray is an excellent objective measure of quality assurance in FS. NME can perform FS with comparable completion rates and accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Studies have shown correct identification of extent of examination in 50-75% of cases. [15,16] If we make the assumption that the reported extent of examination is accurate, these data are therefore consistent with the concept that an acceptable depth is the extent of examination that is reached within a reasonable time without causing excessive discomfort. In general, "easier procedures" continue to the splenic flexure/transverse colon and more "difficult procedures" only to the sigmoid colon.…”
Section: Discussionsupporting
confidence: 70%
“…Studies have shown correct identification of extent of examination in 50-75% of cases. [15,16] If we make the assumption that the reported extent of examination is accurate, these data are therefore consistent with the concept that an acceptable depth is the extent of examination that is reached within a reasonable time without causing excessive discomfort. In general, "easier procedures" continue to the splenic flexure/transverse colon and more "difficult procedures" only to the sigmoid colon.…”
Section: Discussionsupporting
confidence: 70%
“…There are two possible explanations why these cancers were not found on FS. Firstly the depth of insertion might not have been correctly assessed by the endoscopist as this is a common problem [23]. Secondly these could be true misses which are sometimes related to poor bowel preparation [25], which was encountered in 15% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…As there are no landmarks within the left hemi-colon that allow exact confirmation of depth of insertion of the instruments, endoscopists often find it difficult to determine whether the splenic flexure has been reached. A study by Maleskar et al [23] using abdominal radiography to locate a radio-opaque endoclip placed at the deepest point of insertion during FS showed that an accurate assessment of position was achieved in only 31–75% of cases and only 73% of FS were judged to be complete. Painter et al [24] used magnetic endoscopic imaging to determine the depth of insertion in 117 FS.…”
Section: Discussionmentioning
confidence: 99%
“…The Joint Advisory Group (JAG) [10] in endoscopy advises that completion rates of FS should be to the descending colon and are achievable in 90% of cases. There is a wide variation in operator perception of completion of an adequate FS [11]. The technique of endomucosal clips followed by a plain abdominal film has been shown to be a satisfactory and safe objective marker of completion of an adequate FS; however, this may not be appropriate for routine clinical practice [11].…”
Section: Symptoms Of Change In Bowel Habitmentioning
confidence: 99%